2008
DOI: 10.1128/aac.00439-08
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Phenylthiazolyl-Bearing Hydroxamate-Based Histone Deacetylase Inhibitors

Abstract: The antimalarial activity and pharmacology of a series of phenylthiazolyl-bearing hydroxamate-based histone deacetylase inhibitors (HDACIs) was evaluated. In in vitro growth inhibition assays approximately 50 analogs were evaluated against four drug resistant strains of Plasmodium falciparum. The range of 50% inhibitory concentrations (IC 50 s) was 0.0005 to >1 M. Five analogs exhibited IC 50 s of <3 nM, and three of these exhibited selectivity indices of >600. The most potent compound, WR301801 (YC-2-88) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 37 publications
3
106
0
Order By: Relevance
“…We and others have also demonstrated that hyperacetylation of parasite histone and nonhistone proteins and global transcriptional alterations are a functional consequence of HDAC inhibitor exposure in asexual stage parasites (31,32,58,63,69,73,75). This is consistent with a mode of action of this class of compounds that targets HDAC enzymes.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We and others have also demonstrated that hyperacetylation of parasite histone and nonhistone proteins and global transcriptional alterations are a functional consequence of HDAC inhibitor exposure in asexual stage parasites (31,32,58,63,69,73,75). This is consistent with a mode of action of this class of compounds that targets HDAC enzymes.…”
Section: Discussionsupporting
confidence: 61%
“…TSA and SAHA (Fig. 3) are canonical paninhibitors that act on class I/II eukaryotic HDACs 1 to 9 with roughly equal potency (60) and have previously been shown to have potent inhibitory activity against asexual blood-stage P. falciparum parasites (Table 1) (61)(62)(63). The third HDAC inhibitor tested, CAY10603 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The HAT inhibitor anacardic acid is also effective against parasites in culture, although with an IC 50 of >30 µM (23). Inhibition of parasite HDACs has provided more potent compounds against parasite growth and proliferation (26)(27)(28)46). For example, parasite killing by apicidin is reported with an IC 90 of 90 nM, and the hydroxamate trichostatin A has been shown to inhibit parasite growth with an IC 50 of ∼10 nM (47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, parasite killing by apicidin is reported with an IC 90 of 90 nM, and the hydroxamate trichostatin A has been shown to inhibit parasite growth with an IC 50 of ∼10 nM (47). Further refinement of the hydroxamates has produced increasingly efficacious compounds for parasite killing, with mixed consequences with regard to parasite specificity and in vivo activity (26)(27)(28). However, although HDAC inhibitors have progressed into clinical practice for the treatment of certain types of tumors, there are still significant questions over whether their strong antitumorogenic efficacy relates to a truly epigenetic effect-i.e., effect gene transcription although hyperacetylation of histones (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation